Microwave-Absorbing Catalysts in Catalytic Reactions of Biofuel Production - Chia S.R.; Nomanbhay S.; Milano J.; Chew K.W.; Tan C.-H.; Khoo K.S. (MDPI, 2023)
Ammonia; Biofuels; Catalysis; Electric fields; Environmental technology; Microwaves; Oils and fats; Signal processing; Bio-energy; Biofuel production; Catalyst synthesis; Catalytic reactions; Environmental issues; Green technology; Microwave absorbing; Microwave technology; Product yields; ]+ catalyst; Catalysts